VARIABILITY OF GEOLOGICAL AND ENGINEERING CONDITIONS IN RIVER VALLEYS: THE EXAMPLE OF THE UPPER VISTULA RIVER VALLEY - LABAK-MECHOWSKA, EWA (Bulletin of Geography. Physical Geography Series, 2015)
Fluctuations in groundwater levels are usually associated with the seasonal variability of precipitation and evapotranspiration. This has an effect on the carrying capacity of soil and on foundation engineering structures in river valleys. The analysis concerns the example of the Upper Vistula River valley. It presents the geological, groundwater and geological engineering conditions of the researched area through seasonal variations in groundwater level. Based on the results of soil and groundwater analyses, a preliminary assessment was made of the bearing capacity and aggressiveness of the water. An analysis of steel and concrete construction elements was carried out. It was estimated that precipitation has an influence on the strength parameters of soil. With a rise of the groundwater table, physical and mechanical parameters deteriorate. However, a drop in the level of the groundwater table causes an improvement in the strength parameters of soil.